Peningkatan Hasil Belajar Siswa Kelas IV PAI Melalui Model Active Knowledge Sharing di SDN 02 Simpang Tiga Cubadak - Zuryatina, Zuryatina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of 4th grade students in Islamic Religious Education (PAI) through the Active Knowledge Sharing model at SDN 02 Simpang Tiga Cubadak. Based on observations, several issues were identified in PAI learning, such as low student engagement, lack of responsibility in completing exercises, and poor academic performance. This research uses a Classroom Action Research (CAR) approach, focusing on improving students’ learning outcomes in the cognitive domain, specifically in the knowledge aspect (C1). The Active Knowledge Sharing model was applied to enhance student interaction, encourage knowledge sharing among students, and foster collaboration in problem-solving. The results of this study are expected to show an improvement in student learning outcomes as well as increased student activity and involvement in PAI lessons.